Analisis Perbandingan Teoritis Performansi Daya Mesin Mobil dan Konsumsi Bahan Bakar Spesifik Berteknologi VVT-i dan Non VVT-i - Yudhi Chandra Dwiaji; Oka Mahendra (Journal of Applied Mechanical Engineering and Renewable Energy, 2021)
VVT-i (Variable Valve Timing with Intelligent) technology basically works to optimize engine torque at every speed and driving conditions. The mechanism will eventually produce more efficient fuel consumption and lower exhaust emissions. The workings of VVT-i technology are quite simple, namely to calculate the optimal valve opening time, the ECU (Electronic Control Unit) will adjust the engine speed, air intake volume, throttle position and water temperature. In order for the valve timing target to always be realized, the crankshaft position sensor provides a signal that is a correction response. This VVT-i system will correct valve timing or fuel and air inlet lines. Adapted to the gas pedal footing and load borne to produce optimal torque in each rotation and engine load. This technology is also claimed to have excess power that is far more optimal and saves fuel consumption, and is environmentally friendly.